Grin & share it! : more laugh lines for educators - Hodges, Diane (Diane Marie) (Corwin Press, 2008)
Covering children, teaching, ""school daze, "" college, and special occasions, this humorous collection adds fun to the job, spices up communication, and enlivens the school environment.